Intercultural Communication in Complex Interactions - Platica, Adina (New Trends in Psychology, 2024)
The article addresses the complexity and importance of intercultural communication in the context of globalization and global interdependence. Two perspectives of intercultural communication stand out: interaction between different societies and interactions between cultural or ethnic groups within the same society. The authors discuss the communicative process as being more than the transmission of messages, involving the interpretation of meanings, contexts and intentions. Still, despite cultural differences, interpersonal communication remains at the core of intercultural interaction and requires specific skills for success. Intercultural communication skills are essential for effectively navigating interactions. The authors describe intercultural communication as a dynamic process in which different thought processes, values, customs and languages intersect. The role of the psychologist in enhancing intercultural communication, providing individual counselling and mediation in conflict resolution is explored. It highlights the importance of understanding cultural barriers, such as prejudice and stereotyping, and the role of psychologists as guides and facilitators in the intercultural communication process.